Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Servis Handphone Pada Toko Kandilo Cell Com di Tanah Grogot - Amir Hamzah; Ainun Ainun; Nurul Putri Muliyana (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
The aim of this research is to determine the simultaneous and partial influence of the Service Quality (X) variable consisting of Reliability (X1), Responsiveness (X2), Assurance (X3), Empathy (X4), and Physical Evidence (X5) on Satisfaction Consumer (Y) Mobile Phone Service at the Kandilo Cell Com Shop in Tanah Grogot.The samples in this study were consumers who serviced cellphones at the Kandilo Cell Com Shop in Tanah Grogot in June and July 2023 using an incidental sampling technique and the number of samples obtained was 70 people. Consumers as the sample in this study were given a questionnaire consisting of 22 statements. Responses to the questionnaire were tested for validity and reliability before multiple linear regression analysis was carried out.Next, partial testing was carried out by looking at the t-count value for each service quality variable consisting of Reliability (X1), Responsiveness (X2), Assurance (X3), Empathy (X4), and Physical Evidence (X5). Each amounting to 4,878; 2,912; 2,805; 3,268; 1.126 which when compared with ttable of 1.997, then reliability (X1), responsiveness (X2), guarantee (X3), and empathy (X4) influence consumer satisfaction (Y) of cellphone service at the Kandilo Cell Com Store in Tanah Grogot because of the value tcount > ttable. Meanwhile, physical evidence (X5) has no effect on consumer satisfaction (Y) with cellphone service at the Kandilo Cell Com Shop in Tanah Grogot because the calculated t value < t table. So the most dominant influence on consumer satisfaction (Y) of cellphone service at the Kandilo Cell Com Shop is the Reliability variable (X1) because the tcount is the highest.